Home violence as a social problem in modern Ukraine - Вітковська, І. М.; Потапенко, М. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2021)
The article is devoted to the analysis of the problem of home violence in modern Ukraine and the peculiarities of the state social policy for its solution, because today home violence is a common problem among all segments of the population around the world. According to the National Police of Ukraine, on average during 2020, one person suffered from home violence every three hours. The article analyzes the results of sociological research conducted in Ukraine during 20192020 on the prevalence of various forms of violence and the impact of COVID-19 on the number of cases of home violence and more. Based on the secondary analysis of the results of empirical sociological research, it is determined that the most common types of home violence in Ukraine are physical and psychological. The increase in home violence is due to the introduction of quarantine, forcing victims to stay with the perpetrator. This has made it difficult to access legal aid and social services, as providing legal aid remotely (online, by telephone, etc.) is not effective enough when it comes to home violence cases. Also, based on the secondary analysis of the results of empirical sociological research, it was determined that there is a positive trend in the number of complaints of victims of home violence to the police. This is due to the fact that in recent years there have been changes in Ukrainian legislation, information campaigns against home violence have become active, and the work of law enforcement agencies with social services and NGOs has been established.